Karakteristik Morfofungsi Skelet Ekstremitas Kaki Soa Layar (Hydrosaurus amboinensis) - Simangunsong, Yanri R.N.; Novelina, Savitri; Supratikno, Supratikno; Cahyadi, Danang C.; Nisa’, Chairun; Setijanto, Heru; Agungpriyono, Srihadi; Nurhidayat, Nurhidayat (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
The Sailfin lizard is a lizard that has a semi-aquatic life and has a sail fin on its tail. These lizards can be found in habitats close to water such as rivers, lakes, and estuaries of mangrove forests. This study aimed to observe the morphofunctional characteristic of the appendicular skeleton of Sailfin Lizard (Hydrosaurus amboinensis), associated with their function and behavior. The appendicular skeleton of the Sailfin lizard was studied morphofunctional by observing and measuring the bones that make up the extremities. The naming of bones and their parts is based on the Nomina Anatomica Veterinaria 2017 and other journals. The clavicle and interclavicle bones are located anterior to the scapula coracoid which has a convex shape. The patella ulnar bone is found at the humeroulnar joint and the radius et ulna bones have a relatively long antebrachial interosseous space. On the hind legs, the coxal bone has a relatively broad acetabulum, two lunula bones and patellar mineralization are found at the craniodorsal of the femorotibiofibular joint, and tibia et fibula bones have a relatively long crural interosseous space. The palmar part of the carpal bone is found in the palmar sesamoid bone, while the tarsi bones have a fused astragalus and calcaneus bones to become astragalocalcaneus bones. The pedis skeleton's size is relatively long compared to the manus skeleton and has a different middle phalanx bone. The extremity skeletal structure allows the Sailfin Lizard to do movements such as walking, running, climbing, running on water, and swimming.Key words: appendicular skeleton; morphofunction; Sailfin lizard.